Near-infrared cathodoluminescence of Xe2 excimers in dense gaseous mixtures - Borghesani, A. F.; Carugno, G.; Chiossi, F. (Frontiers in Detector Science and Technology, 2025)
We report new spectroscopic measurements of the near-infrared fluorescence band of electron-beam excited Xe2 excimers as a function of the gas density in several gaseous mixtures of different Xe concentrations at room temperature. We have used He, Ar, and N2 as buffer gases, with the Xe concentrations in the mixtures ranging from approximately 8% up to 80%. The investigated density range extends up to 10 times the density Nig of the ideal gas at standard temperature and pressure (Nig≈2.5×1025m−3). In all mixtures, we have observed that the wavelength of the centroid of the infrared excimer band is shifted toward longer wavelengths as the gas density is increased, in a manner similar to what was originally observed in pure Xe gas and an Ar–Xe mixture. The strength of the redshift depends on the Xe concentrations in the mixture and the nature of the buffer gas and is very well rationalized by taking into account both the classical dielectric screening effect due to the gaseous environment and the density-dependent quantum shift of the energy of the optically active electron in the Xe2 molecule, provided that the contributions of the two gaseous species in the mixture are weighted by applying the laws of ideal gaseous mixtures.